(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Honey bees play a vital role in maintaining ecosystems and supporting agricultural practices worldwide. In this comprehensive review, we highlight the importance of honey bees by examining their various contributions to ecosystems and agriculture. We discuss the key ecological functions of honey bees, including pollination, seed dispersal, and nutrient cycling, which are essential for the sustainability of natural systems.